2021
DOI: 10.1186/s12884-021-03544-8
|View full text |Cite
|
Sign up to set email alerts
|

The need for additional mental health support for women in the postpartum period in the times of epidemic crisis

Abstract: Background This retrospective study aimed to identify possible intensification of mental health difficulties among women seeking support in the postpartum period during the epidemic state in Poland. We assumed that the epidemic crisis, social isolation, and restrictions in hospitals which affect pregnant and postpartum women - lack of family labors, lack of the possibility to be with the newborn when he/she is hospitalized, may increase fear and reduce psychosocial resources of women, hinder th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
2
35
0
5
Order By: Relevance
“…During the pandemic, due to new hospital restrictions, expectant mothers will have to go through higher levels of stress and fear as they will now have to cope alone as no spouse or companion is allowed to be in the delivery room to support them [ 6 ]. Studies have shown that support from loved ones is a mediator of fear of childbirth [ 24 ], but in the COVID-19 pandemic, family births were suspended in many countries, and women were deprived of this direct support. Fear and lack of support were predictors of fear of childbirth [ 22 , 35 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, due to new hospital restrictions, expectant mothers will have to go through higher levels of stress and fear as they will now have to cope alone as no spouse or companion is allowed to be in the delivery room to support them [ 6 ]. Studies have shown that support from loved ones is a mediator of fear of childbirth [ 24 ], but in the COVID-19 pandemic, family births were suspended in many countries, and women were deprived of this direct support. Fear and lack of support were predictors of fear of childbirth [ 22 , 35 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that fear of childbirth is associated with the severity of general anxiety [ 20 , 21 ], and that anxiety as a trait is its predictor [ 22 ]. Studies have also shown that support from loved ones is a mediator of fear of childbirth [ 22 , 23 , 24 ], while during a pandemic, family births were banned and women were deprived of this direct support.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional meetings were also an opportunity for physical activity and practical physical training in preparation for childbirth [ 28 ]. Mothers may need additional mental health support, as Chrzan-Dętkoś et al stated [ 29 ], and as professionals and caregivers, we feel responsible to indicate to them the proper solutions and support sources.…”
Section: Discussionmentioning
confidence: 99%
“…Desta forma, dificultam o equilíbrio entre vida profissional e pessoal, desencadeiam conflitos e interferem na adaptação à vida com um novo bebê. Assim, uma crise epidêmica pode limitar parte dos recursos psicológicos que constroem a saúde mental da mulher no período pós-parto (Chrzan-Dętkoś et al 2021).…”
Section: Introductionunclassified